2008
DOI: 10.1086/588757
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Dynamics of Fecal Corticosterone in Male Great Gerbils (Rhombomys opimus Licht.): Effects of Environment and Social Demography

Abstract: We examined the relationship among seasonal characteristics of climate, food, and population demography (social structure) and fecal corticosterone (CORT) concentrations over 6 yr in adult males of an arid-adapted species, the great gerbil (Rhombomys opimus Licht., Gerbillidae, Rodentia), as a measure of chronic stress in high, low, and recovering population densities. Results showed yearly differences in the seasonal means of CORT, with the highest concentrations in the year of the highest population density.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…homeostatic levels of hormones) affect the performance of animals in the wild. Results from these rare studies remain equivocal (Rogovin et al 2003, 2008, Altmann et al 2004, Ethan Pride 2005, Cabezas et al 2007, Pauli and Buskirk 2007, Pedersen and Greives 2008, Pinho et al 2019), which could be explained by the complex influence of environmental conditions (Henderson et al 2017). When resources are limited, increased energy demands can be detrimental by resulting in high levels of GC and allostatic overload.…”
Section: Introductionmentioning
confidence: 99%
“…homeostatic levels of hormones) affect the performance of animals in the wild. Results from these rare studies remain equivocal (Rogovin et al 2003, 2008, Altmann et al 2004, Ethan Pride 2005, Cabezas et al 2007, Pauli and Buskirk 2007, Pedersen and Greives 2008, Pinho et al 2019), which could be explained by the complex influence of environmental conditions (Henderson et al 2017). When resources are limited, increased energy demands can be detrimental by resulting in high levels of GC and allostatic overload.…”
Section: Introductionmentioning
confidence: 99%
“…The best way to answer these questions and to assess how the stress response of animals changes over time would be to collect multiple droppings per animal without pooling them, making a comparison between maximum and minimum cortisol concentrations possible. For example, Rogovin et al (2008) investigated faecal samples collected from trapped great gerbils (Rhombomys opimus) every 30 minutes during two hours of confinement, but they did not detect any corticosterone response related to time in the trap. In the same study, they also analysed seasonal and between-year variation of corticosterone levels, and reported average concentrations of 1.6 -1.85 ng g -1 faeces, which is higher than the cortisol concentrations detected in our samples with the medians being 0.232 ng g -1 for non-trapped and 0.247 ng g -1 for trapped individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the effect of environmental and individual factors in the levels of metabolites of cortisol in G. agilis faecal samples found that dry season has a strong influence on the FGC in the studied population. There is evidence that the adrenal activity associated with a stress response increases during dry seasons in wild animal populations, due to food and water shortage that act as stressors, elevating GCs levels in wild animals ( Rogovin et al , 2008 ; Davies et al , 2013 ; Cizauskas et al , 2015 ). Previous research with the studied G. agilis population found a reduction in food availability during the mid-dry season ( de Camargo et al , 2014 ; Lopes and Leiner, 2015 ), as expected in cerrado and savannah habitats.…”
Section: Discussionmentioning
confidence: 99%